Analysis of the Application of Jarimatika Learning Media in Mathematics Subjects at Elementary School - Nihayatul Wafiroh; Dya Qurotul A'yun (Indonesian Journal of Basic Education, 2023)
For elementary school students, math is a subject that is considered difficult and boring. Jarimatika is a learning media that can facilitate students in counting both addition, subtraction, multiplication, division. The purpose of this research is to analyze the effectiveness of the application of jarimatika learning media in mathematics subjects in elementary schools. This research uses a type of literature review research method. The data collection technique used is using the results of research obtained from several journals, then analyzed and processed by researchers, and found an increase from the application of jarimatika media in mathematics subjects. Based on the data that has been analyzed, it shows that the use of jarimatika media in mathematics subjects can facilitate students in calculating addition, subtraction, multiplication, and division so that it has a positive influence on students' cognitive learning outcomes. This is indicated by the average learning outcomes obtained in math subjects which is 81.317.